Research on Deastringency of Raw Chestnut Rose Juice and Preparation of Its Blended Fruit-Vegetable Juice with Pear and Pumpkin - Jiaxing JIN; Haijuan ZHANG; Hualing YUE; Yan SONG; Hongxia ZHANG; Hongmei LIAO (Shipin gongye ke-ji, 2022)
Objective: To solve the problem of sour taste in raw chestnut rose juice, and to develop its blended fruit-vegetable juice with good taste quality, sweet and sour taste and high stability. Methods: The raw chestnut rose juice was first deastringented with gelatin adsorption or β-cyclodextrin embedding, and then it was blended with freshly prepared pear juice and pumpkin pulp, finally the pasteurization parameters of blended fruit-vegetable juice were optimized. Results: By adding 0.5% gelatin, the tannin removal rate of raw chestnut rose juice could reach 63.00%. According to the sensory evaluation results and basic physical and chemical indexes, the optimal ratio of compound fruit and vegetable juice was determined as follows: The volume ratio of golden thorn pear juice:pear juice:pumpkin pulp was 34:40:26. As the blended fruit-vegetable juice was subjected to pasteurization at 85 °C for 3 min, total viable bacteria of it was1.38 lg CFU/mL, and the counts of yeasts and molds were under the detect limitation (<1 CFU/mL). There were 2.33% and 5.98% reduction of soluble solid content and total acid of the blended juice, respectively. And 67.8% superoxide dismutase was retained. The retention rates of reduced vitamin C (VC) and total VC were 8.72% and 80.3%, respectively. However, a viable browning of blended juice occurred after pasteurization. Conclusion: A blended chestnut rose fruit-vegetable juice with good taste and high nutritional value was developed by deastringency treatment of raw cloudy juice and further more blending with proper fruit-vegetable juice or pulp. The obtained results would provide primary technical suggestions for the deep processing of chestnut rose juice in the future.